Anatomical variations of the aortic arch in a sample of Colombian population (2017)
Introduction: The aortic arch (AA) is the origin of the vascular structures that supply the upper limbs and the brain. Up to eight different types of distributions have been described with clinical and surgical implications.Objective: To determine the frequency of anatomical variations of the AA, and to establish the vascular diameters of its branches in a sample of Colombian population.Materials and methods: A descriptive cross-sectional study was conducted by dissecting 35 cervicothoracic grafts obtained through convenience sampling.Results: The distribution of AA was similar to that reported in Colombia and other countries, being Type I the most frequent, followed by Type II or bovine arch. The vascular diameters showed results similar to those obtained in the Colombian population, but evidently lower than those reported in international studies.Conclusion: Although the frequency of AA types in the Colombian population happen to be similar to those in other countries, the vascular diameters in Colombia are smaller.